Between Money and the Planet? The Interests of Post-colonial Countries in Climate Negotiations - Elbinsar Purba (Andalas Institute of International Studies UNAND, 2024)
This paper explores the interests of post-colonial countries in climate negotiations. It does so by analysing what they need and demand as a consequence of injustice and damages caused by colonialism, which have not been extensively discussed in the current literature. Using content analysis as a methodological approach, the author collected and examined country statements delivered at the Conferences of the Parties (COP) of the United Nations Framework Convention on Climate Change (UNFCCC). The analysis reveals that there are three needs and three demands that commonly lie in the interest of formerly colonised countries. Among them, securing financial resources stands high in their priority. However, this does not mean that provision of funding lessens their perception of historical injustice. They still demand for substantive actions from developed countries to correct the past wrongdoings. While some experts suggest transfer of more resources from the Global North to the Global South to ease the climate decision making process, this paper highlights that although such measure might help build trust, it does not necessarily break the deadlock in climate negotiations.